Assembly of Protein-Based Hollow Spheres Encapsulating a Therapeutic Factor - Kraskiewicz, Honorata (American Chemical Society, 2013)
[Image: see text] Neurotrophins, as important regulators of neural development, function, and survival, have a therapeutic potential to repair damaged neurons. However, a controlled delivery of therapeutic molecules to injured tissue remains one of the greatest challenges facing the translation of novel drug therapeutics field. This study presents the development of an innovative protein–protein delivery technology of nerve growth factor (NGF) by an electrostatically assembled protein-based (collagen) reservoir system that can be directly injected into the injury site and provide long-term release of the therapeutic. A protein-based biomimetic hollow reservoir system was fabricated using a template method. The capability of neurotrophins to localize in these reservoir systems was confirmed by confocal images of fluorescently labeled collagen and NGF. In addition, high loading efficiency of the reservoir system was proven using ELISA. By comparing release profile from microspheres with varying cross-linking, highly cross-linked collagen spheres were chosen as they have the slowest release rate. Finally, biological activity of released NGF was assessed using rat pheochromocytoma (PC12) cell line and primary rat dorsal root ganglion (DRG) cell bioassay where cell treatment with NGF-loaded reservoirs induced significant neuronal outgrowth, similar to that seen in NGF treated controls. Data presented here highlights the potential of a high capacity reservoir-growth factor technology as a promising therapeutic treatment for neuroregenerative applications and other neurodegenerative diseases.